Disruption of columnar and laminar cognitive processing in primate prefrontal cortex following cocaine exposure - Opris, Ioan; Gerhardt, Greg A.; Hampson, Robert E.; Deadwyler, Sam A. (Frontiers in Systems Neuroscience, 2015)
Prefrontal cortical activity in primate brain plays a critical role in cognitive processes involving working memory and the executive control of behavior. Groups of prefrontal cortical neurons within specified cortical layers along cortical minicolumns differentially generate inter- and intra-laminar firing to process relevant information for goal oriented behavior. However, it is not yet understood how cocaine modulates such differential firing in prefrontal cortical layers. Rhesus macaque nonhuman primates (NHPs) were trained in a visual delayed match-to-sample (DMS) task while the activity of prefrontal cortical neurons (areas 46, 8 and 6) was recorded simultaneously with a custom multielectrode array in cell layers 2/3 and 5. Animals were reinforced with juice for correct responses. The first half of the recording session (control) was conducted following saline injection and in the second half of the same session cocaine was administered. Prefrontal neuron activity with respect to inter- and intra-laminar firing in layers 2/3 and 5 was assessed in the DMS task before and after the injection of cocaine. Results showed that firing rates of both pyramidal cells and interneurons increased on Match phase presentation and the Match response in both control and cocaine halves of the session. Differential firing under cocaine vs. control in the Match phase was increased for interneurons but decreased for pyramidal cells. In addition, functional` interactions between prefrontal pyramidal cells in layer 2/3 and 5 decreased while intra-laminar cross-correlations in both layers increased. These neural recordings demonstrate that prefrontal neurons differentially encode and process information within and between cortical cell layers via cortical columns which is disrupted in a differential manner by cocaine administration.